Políticas da escrita em Michel Foucault - Silva, Fabrício Tavares Santos (2023)
The theme of writing appears in Michel Foucault's thought from two problematic axes. First, an understanding of literary writing as desubjectivation: as an experience, therefore, of dissolution of the subject. Secondly, writing conceived as a work of attention to oneself, as a practice of constituting and transforming oneself by the subject: conceived, therefore, as a technique of subjectivation. The two axes presuppose different problematizations and cuts in Foucault's thought. Our first cut is based on an analysis of Foucault's relationship with literary discourse in his works in the sixties, as well as the transformations of this relationship in the following decade. If, on the one hand, literature is conceived at that first moment as a counter-discourse in relation to the human sciences, in the seventies it will be inserted by Foucault in the broader context of strategic devices, devices of power that make up modern disciplinary institutions. Our second cut, therefore, concerns the notion of self-writing, which appears to be linked to Foucault's investigations into the constitution of an ethical subject in Greco-Roman antiquity and early Christianity, as well as its possible resonances with the long historical formation of the conception of a knowing subject in Modernity. We are interested in understanding, from there, the very relationship that Foucault establishes with writing in his intellectual trajectory and how this relationship can serve to think of philosophical activity itself as a literary activity